Analysis of the Influence of the Use of Instagram Social Media in the Promotion - Elsa Triana; Ripka Octaviani; Sabrina Tamba; Putri Sosanti Sembiring (Generasi Sains Indonesia, 2025)
This study aims to analyze the influence of Instagram-based tourism promotion on destination awareness and visitation intention toward Lake Toba in the post-pandemic tourism context. A quantitative survey approach was employed involving 49 respondents who actively use Instagram as a source of tourism information. Data were collected through structured questionnaires and analyzed using descriptive statistical techniques. The findings reveal that Instagram serves as a primary tourism information source for most respondents and significantly contributes to destination awareness, travel interest, and destination consideration. More than 80% of respondents reported increased interest in visiting Lake Toba after exposure to promotional content, while positive perceptions of content credibility and relevance strengthened destination image and recommendation intentions. The study also demonstrates the role of Instagram in encouraging electronic word-of-mouth behavior, thereby extending destination visibility beyond direct promotional efforts. These findings highlight the importance of visual social media as a strategic tool for destination branding and tourism marketing. The study provides theoretical and practical insights for tourism stakeholders seeking to enhance destination competitiveness through digital promotion strategies.